Do behavioral drivers matter for healthcare decision-making in times of Crisis? A study of low-income women in El Salvador during the COVID-19 pandemic - Pedro Bernal; Giuliana Daga; Lajos Kossuth; Florencia López Bóo (Inter-American Development Bank (IDB), 2023)
Understanding health-seeking behaviors and their drivers is key for governments to manage health policies. There is a growing literature on the role of cognitive biases and heuristics in health and care-seeking behaviors, but little is known of how they might be influenced during a context of heightened anxiety and uncertainty. This study analyzes the relationship between four behavioral predictors - the internal locus of control, impatience, optimism bias, and aspirations - and healthcare decisions among low-income women in El Salvador. We find positive associations between 'internal locus of control and preventive health behaviors during the COVID-19 pandemic (use of masks, distance, hand washing, and COVID-19 vaccination) and in general (prenatal checkups, iron-rich diets for children and hypertension tests). Measures of impatience negatively correlate with COVID-19 prevention behaviors and mothers' micronutrient treatment adherence for children, and optimism bias and educational aspirations with healthcare-seeking behaviors during the COVID-19 pandemic. Some associations were more robust during the pandemic, suggesting that feelings of uncertainty and stress could enhance behavioral drivers' influence on health-related behaviors, a novel and relevant finding in the literature relevant for the design of policy responses for future shocks.
Keywords: I12; D10; D91; I30; 330; healthcare decision-making; behavioral economics; COVID-19; low-income setting; Latin America; El Salvador